SCIENCE PRACTICUM ACTIVITIES THROUGH SEPARATION OF LEAVES PIGMENTS BY PAPER CHROMATOGRAPHY IN JUNIOR HIGH SCHOOL - Nabilah, Shofa; Riandi, Riandi; Prima, Eka Cahya (JOURNAL OF SCIENCE EDUCATION AND PRACTICE, 2025)
The material on mixture separation is still challenging for students to grasp, students still do not fully understand the concept of chromatography. One way for students to gather information is by planning and carrying out experiments or practicum activities. The author wants to provide experience to students through experimental activities through separation of leaves pigments by paper chromatography with simple method. The method used is the development of an experiment-based practicum learning method on separation of mixture material which was carried out in class 7th grade students at junior high school level. The result of paper chromatography can separate pigments present in leaves. The pigments found in Iresine diffusa leaves are chlorophyll-a characterized by the green color, chlorophyll-b characterized by the yellow-green color, and carotene characterized by the orange color. However, the polarity of the solvent does not influence the Rf value in leaf pigments, as the range of Rf values remains consistent with other research results, even though the components of the solvent used are different. Students' responses, in terms of comprehension of the material and motivation to learn during this practical activity, also show high levels, with an average of 74.43%.